1998
DOI: 10.1074/jbc.273.41.26962
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin Is an Activator of Insulin Receptor Signaling

Abstract: Recent data have demonstrated that caveolin, a major structural protein of caveolae, negatively regulates signaling molecules localized to caveolae. The interaction of caveolin with several caveolae-associated signaling proteins is mediated by the binding of the scaffolding region of caveolin to a hydrophobic amino acid-containing region within the regulated proteins. The presence of a similar motif within the insulin receptor kinase prompted us to investigate the caveolar localization and regulation of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
214
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(230 citation statements)
references
References 42 publications
13
214
1
2
Order By: Relevance
“…1998; Yamamoto et al. 1998). Our co‐IP and FRET data in HL‐1 cardiomyocytes provide further support that the IR and CAV3 are in close proximity.…”
Section: Discussionmentioning
confidence: 99%
“…1998; Yamamoto et al. 1998). Our co‐IP and FRET data in HL‐1 cardiomyocytes provide further support that the IR and CAV3 are in close proximity.…”
Section: Discussionmentioning
confidence: 99%
“…SCP-2) cholesterol binding proteins preferentially donate or extract cholesterol from cholesterol-rich, but not cholesterol-poor, microdomains (26,27,136,137,172). The microdomain/lipid raft concept, despite controversy in details, provides a framework for biologists studying localization and function of membrane protein receptors, transporters, and downstream signaling molecules that regulate uptake of cholesterol (86,87,, fatty acids (240)(241)(242), glucose (243)(244)(245)(246)(247)(248)(249)(250)(251)(252)(253)(254), and other activities (216,(255)(256)(257)(258)(259)(260). Cholesterol-poor microdomain preferring cholesterol analogs: BODIPY-coprostanol analog 3; BODIPY-cholesterol analog LZ110a; 22-NBD-cholesterol.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Cav-1 expression pattern is similar to that observed in adipose tissue in previous studies, while Cav-2 behaves in the opposite way [26,27], suggesting that they are inversely regulated. In adipocytes Cav-1 co-localizes with IR and positively regulates the activation of IR upon insulin stimulation [28], but the role of Cav-1 in muscle insulin signalling has received little attention, probably because Cav-3 is the musclespecific isoform. Our results suggest that insulin signalling could be downregulated due to a decrease in Cav-1 and IR phosphorylation, in accordance to other authors that have reported reduced muscle insulin-stimulated glucose uptake after siRNA downregulation of Cav-1 [5].…”
Section: Discussionmentioning
confidence: 99%